Descontento general en toda la tierra y notable daño a la Real Hacienda”: El virrey Francisco de Toledo, su red de criados y el acceso a los bienes de comunidad y censos de indios - Costa, Luis Miguel (2024)
This work is a product of the project Failure. Reversing the Genealogies of Unsuccess, 16th–19th Centuries; REVFAIL (Grant Agreement No. 823998), funded by the European Union’s Horizon 2020 MSCA program